1994
DOI: 10.1016/s0886-3350(13)80159-9
|View full text |Cite
|
Sign up to set email alerts
|

Coring: A potential problem in eye surgery

Abstract: Any needle passing through a rubber stopper can aspirate a core of rubber. This rubber may then be injected into the eye or into the retrobulbar or peribulbar space. Aspirates from a number of syringes were spun down in a centrifuge and examined for microscopic particles. All specimens contained microscopic particles even from half-used bottles of Xylocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This high variance in prevalence is at least partially due to the detection method used. Studies that used microscopy detect coring particles at higher rates [3,4] than studies that did not use microscopy. Other variables have also been reported to potentially affect the rate of coring including the angle at which the needle is inserted into the vial, the use of sharp or blunt tip needles, the use of multiple or single use vials, and the type of stopper [5‐7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This high variance in prevalence is at least partially due to the detection method used. Studies that used microscopy detect coring particles at higher rates [3,4] than studies that did not use microscopy. Other variables have also been reported to potentially affect the rate of coring including the angle at which the needle is inserted into the vial, the use of sharp or blunt tip needles, the use of multiple or single use vials, and the type of stopper [5‐7].…”
Section: Methodsmentioning
confidence: 99%
“…Removing the rubber stopper from the vial could prevent coring but might increase the risk of contamination [3]. Some authors have suggested removing the stopper from the vial using a pliers‐like device [24].…”
Section: Methodsmentioning
confidence: 99%
“…5 Since then only case reports or a few articles with small sample sizes have tried to assess the incidence of this phenomenon. 5,6 Campagna et al described a 10.5% incidence of coring in an experiment with 200 vials. 6 The introduction of blunt needles to reduce accidental skin punctures among healthcare personnel seems to have increased the incidence of coring: Wani et al noted an incidence of 40.2% with blunt needles and 4.2% with sharp needles.…”
Section: Editormentioning
confidence: 99%
“…4 In the literature we can find that the first report of coring dates to 1994 when rubber particles were found inside lidocaine syringes used for retrobulbar anaesthesia. 5 Since then only case reports or a few articles with small sample sizes have tried to assess the incidence of this phenomenon. 5,6 Campagna et al described a 10.5% incidence of coring in an experiment with 200 vials.…”
Section: Editormentioning
confidence: 99%
“…There are no published reports on intra-articular injection of rubber particles available to date. However, embolisms after intravenous drug application was found to be related to vial coring, indicating that intra-articular injections are at risk for vial coring associated complications including septic arthritis [ 11 , [16] , [17] , [18] , [19] ]. Moreover a foreign body reaction could promote rapid destructive osteoarthritis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%